VA staff perceptions of the role of the extended care referral process in home and community-based services versus nursing home use posthospital discharge. Issue 2 (3rd April 2017) - Miller, Edward Alan; Intrator, Orna; Gadbois, Emily; Gidmark, Stefanie; Rudolph, James L.
ABSTRACT: Little is known about how the extended care referral process—its structure and participants—influences Veterans' use of home and community-based services (HCBS) over nursing home care within the Veterans Health Administration (VHA). This study thus characterizes the extended care referral process within the VHA and its impact on HCBS versus nursing home use at hospital discharge. Data derive from 35 semistructured interviews at 12 Veterans Affairs Medical Centers (VAMCs). Findings indicate that the referral process is characterized by a commitment by care teams to consider HCBS if possible, varied practice depending on the clinician that most heavily influences care team recommendations, and care team emphasis on respecting Veteran/family preferences even when they are contrary to care team recommendations. Potential modifications include adopting systematic assessment practices; improving Veteran, family, and provider education; and promoting informed selection through shared decision making.